2023
DOI: 10.1039/d2ta07838d
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling high-performance oxygen-deficient amorphous manganese oxide as the cathode for advanced zinc ion batteries

Abstract: Secondary Zinc-MnO2 batteries represent the climax of aqueous battery technology, earned by their high specific capacity and high-power density. However, Zinc-MnO2 batteries suffer from serious impediments such as capacity fading,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…The loading of Ag in both Ag/MnO 2 and Ag/AlÀ MnO 2 was about 2.5 % according to the ICP-OES results. Moreover, the sharp and intense XRD peaks of Ag/AlÀ MnO 2 match well with the tetragonal α-MnO 2 structure (JCPDS 44-0141) (Figure S1), [13,17] and the Al modification has negligibly affected the lattice parameters of α-MnO 2 (Table S1). Furthermore, the nitrogen adsorptiondesorption isotherms and porosity distribution data indicate that the Ag/AlÀ MnO 2 system retains a similar specific surface area and porous structure as MnO 2 and Ag/MnO 2 (Figure S6, Table S2), which altogether proves that the Al modification on MnO 2 practically does not affect the geometric structure of the Ag/AlÀ MnO 2 catalyst.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The loading of Ag in both Ag/MnO 2 and Ag/AlÀ MnO 2 was about 2.5 % according to the ICP-OES results. Moreover, the sharp and intense XRD peaks of Ag/AlÀ MnO 2 match well with the tetragonal α-MnO 2 structure (JCPDS 44-0141) (Figure S1), [13,17] and the Al modification has negligibly affected the lattice parameters of α-MnO 2 (Table S1). Furthermore, the nitrogen adsorptiondesorption isotherms and porosity distribution data indicate that the Ag/AlÀ MnO 2 system retains a similar specific surface area and porous structure as MnO 2 and Ag/MnO 2 (Figure S6, Table S2), which altogether proves that the Al modification on MnO 2 practically does not affect the geometric structure of the Ag/AlÀ MnO 2 catalyst.…”
Section: Resultssupporting
confidence: 60%
“…Manganese oxide octahedral molecular sieve nanorod, featuring ordered arrays of MnO 6 moieties with shared edges and vertices, have recently attracted increasing attention. [13][14][15][16] Moreover, the MnO 2 materials modified by metal cations, such as Cu, Co, Ag, Ce and Zr were successfully applied to some selective oxidation reactions, by virtue of their distinct porosity, adjustable electronic structure, and abundant internal crystal defects. [17][18][19][20][21][22][23] Yin et al have demonstrated the application of metal-modified MnO 2 for selective oxidation of several hydrocarbons to produce oxygen-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The loading of Ag in both Ag/MnO 2 and Ag/Al−MnO 2 was about 2.5 % according to the ICP‐OES results. Moreover, the sharp and intense XRD peaks of Ag/Al−MnO 2 match well with the tetragonal α‐MnO 2 structure (JCPDS 44‐0141) (Figure S1), [13,17] and the Al modification has negligibly affected the lattice parameters of α‐MnO 2 (Table S1). Furthermore, the nitrogen adsorption‐desorption isotherms and porosity distribution data indicate that the Ag/Al−MnO 2 system retains a similar specific surface area and porous structure as MnO 2 and Ag/MnO 2 (Figure S6, Table S2), which altogether proves that the Al modification on MnO 2 practically does not affect the geometric structure of the Ag/Al−MnO 2 catalyst.…”
Section: Resultssupporting
confidence: 55%
“…Manganese oxide octahedral molecular sieve nanorod, featuring ordered arrays of MnO 6 moieties with shared edges and vertices, have recently attracted increasing attention [13–16] . Moreover, the MnO 2 materials modified by metal cations, such as Cu, Co, Ag, Ce and Zr were successfully applied to some selective oxidation reactions, by virtue of their distinct porosity, adjustable electronic structure, and abundant internal crystal defects [17–23] .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3c, N‐V O ‐ZVO displays capacity output of the initial 497 mAh g −1 at 0.5 A g −1 and 94% capacity retention after 250 cycles, with V O ‐ZVO suffering from a fast capacity decay (426 mAh g −1 at 0.5 A g −1 after 250 cycles) and poor capacity retention (85%). Apparently, N‐V O ‐ZVO exhibits ultra‐high rate performance with 186 mAh g −1 at 100 A g −1 that significantly outperforms reported cathode materials for ZIBs, such as VO X /Mn‐V 2 C, [ 22 ] VO 2 ·0.75H 2 O, [ 23 ] A‐MnO 2 , [ 24 ] and Li@MnVO, [ 25 ] and so on (Figure 3d). Ex situ XRD characterization can provide further detail on the structural evolution of the N‐V O ‐ZVO cathode during charging/discharging process.…”
Section: Resultsmentioning
confidence: 99%